2012
DOI: 10.1007/978-3-642-32009-5_50
|View full text |Cite
|
Sign up to set email alerts
|

Fully Homomorphic Encryption without Modulus Switching from Classical GapSVP

Abstract: We present a new tensoring technique for LWE-based fully homomorphic encryption. While in all previous works, the ciphertext noise grows quadratically (B → B 2 · poly(n)) with every multiplication (before "refreshing"), our noise only grows linearly (B → B · poly(n)).We use this technique to construct a scale-invariant fully homomorphic encryption scheme, whose properties only depend on the ratio between the modulus q and the initial noise level B, and not on their absolute values.Our scheme has a number of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
486
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 769 publications
(592 citation statements)
references
References 20 publications
1
486
0
2
Order By: Relevance
“…In this paper, we continue the line of work of [LMSV12,ZPS12] to present key recovery attacks for the schemes [BV11b,BV11a,GSW13,Bra12]. Our attacks can also be applied to the SHE scheme in [BGV12].…”
Section: Our Contributionsmentioning
confidence: 80%
See 4 more Smart Citations
“…In this paper, we continue the line of work of [LMSV12,ZPS12] to present key recovery attacks for the schemes [BV11b,BV11a,GSW13,Bra12]. Our attacks can also be applied to the SHE scheme in [BGV12].…”
Section: Our Contributionsmentioning
confidence: 80%
“…In this paper, we showed that the SHE schemes from [BV11b,BV11a,BGV12,Bra12,GSW13] suffer from key recovery attacks when the attacker is given access to the decryption oracle. Combining the results from [LMSV12,ZPS12], we now know that most existing SHE schemes suffer from key recovery attacks, and so they are not IND-CCA1 secure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations